Analisa Komparatif Profitabilitas Perusahaan dalam Penerapan PSAK 71 (studi kasus PT Indosat Tbk.) - shyfa, vayolla naurah (COMPETITIVE, 2023)
The latest IFRS implementation which caused the change of PSAK 55 to PSAK 77 to become a new challenge for various corporate sectors in Indonesia The Financial Accounting Standards Board (DSAK) has conveyed related to PSAK 71 since 2017 and its early implementation is allowed, meanwhile DSAK implements related obligations implementation of PSAK 71 in 2020 in stages. PT ISAT Tbk. is one of the companies that carried out early implementation of PSAK 71, namely in 2018. This research is a comparative study with a qualitative approach with secondary data sources, namely the company's financial statements for the 2017-2018 period. With the aim of knowing how to analyze the company's profitability when using PSAK 55 (2017) and when applying PSAK 71 (2018) early. In the research conducted, it was found that the company's profitability ratio decreased in 2018 compared to 2017 before the application of PSAK 71.Keywords: Profitability Analysis, PSAK 71, PSAK 55